The Effect of Tax Awareness, Socialization Taxation, And Tax Sanctions Against Personal Taxpayer Compliance - Nur Hikmah (Journal of Islamic Economy and Community Engagement, 2022)
This study aims to determine the awareness of taxation, socialization of taxation, and tax sanctions affect the compliance of individual taxpayers. The data used are primary data obtained from questionnaires distributed to individual taxpayers. The results of the study indicate that tax awareness and tax sanctions have a positive effect on individual taxpayer compliance, while tax socialization does not affect individual taxpayers.